DNMT3A and TET2 in the Pre-Leukemic Phase of Hematopoietic Disorders - Sato, Hanae; Wheat, Justin C.; Steidl, Ulrich; Ito, Keisuke (Frontiers in Oncology, 2016)
In recent years, advances in next-generation sequencing (NGS) technology have provided the opportunity to detect putative genetic drivers of disease, particularly cancers, with very high sensitivity. This knowledge has substantially improved our understanding of tumor pathogenesis. In hematological malignancies such as acute myeloid leukemia and myelodysplastic syndromes, pioneering work combining multi-parameter flow cytometry and targeted resequencing in leukemia have clearly shown that different classes of mutations appear to be acquired in particular sequences along the hematopoietic differentiation hierarchy. Moreover, as these mutations can be found in “normal” cells recovered during remission and can be detected at relapse, there is strong evidence for the existence of “pre-leukemic” stem cells (pre-LSC). These cells, while phenotypically normal by flow cytometry, morphology, and functional studies, are speculated to be molecularly poised to transform owing to a limited number of predisposing mutations. Identifying these “pre-leukemic” mutations and how they propagate a pre-malignant state has important implications for understanding the etiology of these disorders and for the development of novel therapeutics. NGS studies have found a substantial enrichment for mutations in epigenetic/chromatin remodeling regulators in pre-LSC, and elegant genetic models have confirmed that these mutations can predispose to a variety of hematological malignancies. In this review, we will discuss the current understanding of pre-leukemic biology in myeloid malignancies, and how mutations in two key epigenetic regulators, DNMT3A and TET2, may contribute to disease pathogenesis.